The Role of Advertising in Shaping Consumer Perceptions of Sustainable Brands - Eyada, Bassant (Journal of Ecohumanism, 2024)
This research investigates the pivotal role of advertising in shaping consumer perceptions of sustainable brands, delving into the intricate mechanisms by which advertising strategies influence consumer attitudes and behaviors towards sustainability. Through an extensive review of literature, empirical findings, and prospective research directions, this study illuminates the nuanced landscape of sustainability advertising and its profound implications for marketers and consumers. The research underscores the burgeoning significance of sustainable branding within contemporary marketing paradigms, propelled by the escalating consumer interest in sustainability and ethical consumption. Empirical investigations affirm a robust positive correlation between advertising exposure to sustainable brands and consumer perceptions, underscoring the substantial impact of advertising on molding attitudes and driving purchase behavior. The researcher explores the influence of advertising on consumer perceptions of sustainable brands, through a comprehensive review of literature, qualitative and empirical analysis, investigates the mechanisms by which advertising strategies impact consumer attitudes and behaviors towards sustainable brands, explore theories and concepts that provide insights into the mechanisms by which advertising strategies impact consumer attitudes and behaviors towards sustainable brands. Additionally, present the findings of empirical analysis, which further elucidates these relationships and sheds light on the significant role of advertising in shaping perceptions of sustainability and provide insights for marketers aiming to promote sustainable products and initiatives.